2007
DOI: 10.1186/1742-2094-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: IntroductionAutism is complex neuro-developmental disorder which has a symptomatic diagnosis in patients characterized by disorders in language/communication, behavior, and social interactions. The exact causes for autism are largely unknown, but is has been speculated that immune and inflammatory responses, particularly those of Th2 type, may be involved. Thiazolidinediones (TZDs) are agonists of the peroxisome proliferator activated receptor gamma (PPARγ), a nuclear hormone receptor which modulates insulin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 58 publications
1
53
2
1
Order By: Relevance
“…Furthermore, Adams and coworkers have comprehensively reviewed the link between autism and metabolic disturbances in young and adult autistic patients [25]. Interestingly, another study showed that treatment of autism patients with pioglitazone resulted in improvement of some symptoms, with a stronger effect in younger patients [26]. This is the first report showing that changes in these molecules occur in an age-dependent manner in ASD individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Adams and coworkers have comprehensively reviewed the link between autism and metabolic disturbances in young and adult autistic patients [25]. Interestingly, another study showed that treatment of autism patients with pioglitazone resulted in improvement of some symptoms, with a stronger effect in younger patients [26]. This is the first report showing that changes in these molecules occur in an age-dependent manner in ASD individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MIA mouse offspring treated with antipurinergic therapy (APT) (69, 70) or the gut bacterium Bacteroides fragilis (62) exhibit improved behavioral outcomes. Future studies are needed to explore emerging clinical (114) and preclinical (68, 73, 115) treatments targeting the immune system as a promising area of research for ASD drug discovery efforts.…”
Section: Assessing Validity Of the Mia Modelmentioning
confidence: 99%
“…A preliminary study of the thiazolidinedione, pioglitazone, which has anti-inflammatory properties, causes a significant decrease in irritability, lethargy, stereotypy and hyperactivity in autistic children, with greater effects on younger patients (26). MIA models provide an attractive platform for further testing of such therapies.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%